BIOLOGY AND POPULATION DYNAMICS OF BANANA SHRIMP (Penaeus merguiensis) IN THE TARAKAN WATERS, EAST BORNEO - Duranta D. Kembaren; Ali Suman (Research Center for Fisheries, 2013)
Study of biology and population dynamic of banana shrimp (Penaeus merguiensis) in Tarakan waters, East Borneo was carried out from January to November 2012. The aim of this research was to identify the biological aspects and population dynamics of banana shrimp. For estimating dynamic population, data were analysed using FiSAT II. The result showed that length at first capture (Lc) of banana shrimp by mini trawl (pukat hela) was 35 mm and the size at first maturity (Lm) was 33,86 mm in carapace length. Spawning occured all year around and reached it’s peak in March. The growth coefficient (K) of banana shrimp was 1,45/year with carapace asymptotic length (CL”) of 80 mm. Total mortality rate (Z) and natural mortality rate (M) were 4,85/year and 1,76/year. While fishing mortality rate (F) and exploitation rate (E) were 3,09/year and 0,64, respectively. The exploitation rate of banana shrimp in Tarakan waters tended to be overexploited so that it needed to be managed wisely and carefully by reducing the fishing effort and fishing season especially on spawning season. The recruitment peak of banana shrimp occured in May.